2014
DOI: 10.1111/ppa.12287
|View full text |Cite
|
Sign up to set email alerts
|

Role of strawberry volatile organic compounds in the development of Botrytis cinerea infection

Abstract: Botrytis cinerea, the main pathogen of strawberry, has the ability to remain quiescent in unripe tissue and develop disease symptoms in ripe fruit. As strawberry ripening is characterized by an increase of aroma compounds, the role of volatile emission in the development of infection was investigated. Thirty-five strawberry volatile organic compounds (VOCs) were tested on B. cinerea in vitro and volatile emission was analysed in strawberry harvested at four ripening stages by headspace solid-phase microextract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
4
32
0
1
Order By: Relevance
“…In strawberry, these volatile showed a stimulatory effect on conidial germination of Botrytis cinerea (Neri et al, 2015). In the present study, a marked increase of 6-methyl-5-hepten-1-one was observed in inoculated fruit, even during the first few hours after inoculation, and it was progressive over time particularly at 20 °C, following a similar pattern of the Alternaria rot development.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In strawberry, these volatile showed a stimulatory effect on conidial germination of Botrytis cinerea (Neri et al, 2015). In the present study, a marked increase of 6-methyl-5-hepten-1-one was observed in inoculated fruit, even during the first few hours after inoculation, and it was progressive over time particularly at 20 °C, following a similar pattern of the Alternaria rot development.…”
Section: Discussionsupporting
confidence: 56%
“…Fungi, plants, and fruits produce a variety of volatile metabolites that could act as signals of plant disease (Jansen et al, 2011), or as signaling molecules that play a vital role in the activation of disease resistance mechanisms. Also, could act as antimicrobial agent (Neri et al, 2015), or could serve as markers for the detection of the spoilage pathogens (Vikram et al, 2004;Moalemiyan et al, 2006). In this study, were identified some VMs released from strains of A. alternata growing on PDA plates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigro et al (2000) found that UV-C 254 nm reduces postharvest decay on strawberries. Neri et al (2014) ran a test on thirty-five strawberry volatile organic compounds on B. cinerea in vitro and found that 14 compounds significantly influenced the conidial germination of B. cinerea. Tezotto-Uliana et al (2014) ran a test on pre and post-harvest chitosan coating in order to prolong the shelf life of raspberries.…”
Section: Resultsmentioning
confidence: 99%
“…For some VOCs, the exposure to the higher concentration used in the experiments (12.3 μL L -1 ) reduced the development of Botrytis cinerea. In particular, the aldehydes trans-2-hexenal and nonanal completely inhibited conidial germination and nonanal showed the best reduction of mycelial growth (-66.8%) at this concentration [13]. Nowadays, application of plant volatiles as inhibitory compounds towards fungal pathogens could be another interesting alternative.…”
Section: Introductionmentioning
confidence: 99%